Airborne Residues of Paraquat, Glyphosate and Chlorpyrifos in Rice Fields of Sungai Besar, Selangor, Malaysia - Morshed, Md. Mahbub (2011)
Due to government subsidies and lack of labour, rice farmers in Malaysia generally use large amount of pesticides in a season starting from land preparation until maturity. The intensive use of pesticides has resulted into serious contamination of the environment, because substantial amount of agriculturally applied pesticides have been shown to become airborne during and after application that ultimately cause acute and chronic health hazards to field workers. In this study, airborne residue levels of three widely used pesticides (paraquat, glyphosate, and chlorpyrifos) were determined in two rice seasons (wet and dry) at three sampling locations (Kampung Pasir Panjang, Kampung Simpang Lima and Kampung Sungai Panjang) in Sungai Besar, Malaysia. Air was sampled in 12h day time with a 4h sampling intervals at both pre-and post-spray sampling events by using three simple and low-cost passive samplers (cotton gauze, cellulose filter, and polyurethrane foam (PUF) samplers) and two active samplers (PUF plug and quartz filter cartridges). Moreover, air was pumped in the breathing zone of the spray operator to measure the possible amount of pesticides breathed in during field spraying. For accurate residue analysis of air samples, analytical method validation was performed that showed the fitness of methods for each compound undertaken in this study. Studies on passive sampler’s performance validation showed that the performance of passive samplers were consistent. Satisfactory correlation coefficient (r2 = 0.979) was observed in paired comparison between active and passive sampling methods, and passive sampling showed significantly better performance over active sampling method with respect to airborne residue measurement. Among the three passive air samplers, cotton gauze showed significantly the highest deposition for particle-bound pesticides – paraquat and glyphosate (15.56 and 2.49 ng/cm2, respectively), whereas PUF sampler showed the highest for vapor-bound pesticide – chlorpyrifos (48.80 ng/cm2). In active air samplers, paraquat and glyphosate residues were detected only in quartz fibre filter cartridges (0.52 and 0.10 μg/m3, respectively); on the other hand, chlorpyrifos was detected on PUF plug cartridges (2.54 μg/m3). Data on airborne residue measured in the rice growing area revealed that among the three compounds, glyphosate was measured in the lowest amount in the air followed by paraquat and chlorpyrifos. In day-long sampling events, however, virtually no residue was detected in any of the samples exposed in the pre-event sampling, and obviously, the highest airborne residue was measured during spraying at breathing zone of the spray operator, and subsequently the residue levels were drastically dropped in the postspray sessions. Moreover, in post-spray sampling sessions, the residue level was consistently higher during first 0-4 hours relative to that of second 4-8 hrs sampling events. Furthermore, residue amounts showed spatial (location-wise) as well as seasonal variations during which local environmental conditions, physiochemical properties of the compound and its application technique played very important role on pesticides atmospheric deposition. In comparison between rice seasons, residue amounts measured by passive and active sampling methods showed higher detection in dry season (18.83,8.59 ng/cm2 and 0.76, 0.28 μg/m3 for paraquat; 2.82, 1.03 ng/cm2 and 0.28, 0.06 μg/m3 for glyphosate; 48.62, 19.71 ng/cm2 and 4.19, 1.54 μg/m3 for chlorpyrifos, respectively) than that of wet season (13.68, 4.84 ng/cm2 and 0.56, 0.19 μg/m3 for paraquat; 1.62, 0.55 ng/cm2 and 0.13, 0.00 μg/m3 for glyphosate; 21.28, 9.36 ng/cm2 and 1.79, 0.54 μg/m3 for chlorpyrifos, respectively). However, seasonal variations showed insignificant effects on airborne residue for paraquat and glyphosate, but significant effect for chlorpyrifos. Interestingly, seasonal effect was insignificant for paraquat, glyphosate and chlorpyrifos on respirable residues (109.74, 32.50, 153.50 μg/m3 in wet season and 108.66, 31.73, 186.68 μg/m3 in dry season, respectively) in the air around the spray operator’s breathing zone during spraying in the field. In extrapolated field operators exposure assessment, both potential dermal (5 to 7 and 15 to 30 times, respectively) and inhalation (40 and 100 times, respectively) doses were higher than the proposed acceptable operators exposure level (AOEL) for paraquat and chlorpyrifos, whereas,both doses were far below the proposed AOEL for glyphosate.